PROSES PEMBELAJARAN MATEMATIKA UNTUK SISWA SLOW LEARNER DI KELAS INKLUSI SMP NEGERI 7 KLATEN KELAS VIII - Karina Pramitasari; Budi Usodo; Sri Subanti (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purposes of this research are intended to describe (1) teacher’s strategy in teaching learning activity for slow learner in the inclusive class  of SMPN 7 Klaten, (2) the teaching learning process in the inclusive class  of SMPN 7 Klaten, (3) teacher’s problems in Mathematics teaching learning process in the inclusive class of SMPN 7 Klaten. This research used a qualitative approach in the form of field research. The  subjects of the research are  four participants choosen by using  purposive sampling. They are  a mathematics teacher, a slow learner having special needs and two normal students. The research instruments consist of the researcher as the main instrument, observation sheet as the first supplementary instrumen and interview basic as the second supplementary instrumen. Based on the results of the research, it can be concluded that, as follows: (1) teacher conducted the planning step by designing lesson plan, the teaching learning step and the evaluation/follow up step in the inclusive class as same as what the teacher conducted in the regular class. The difference is situated only at the giving of special attention and the special guidance for slow learner who have special need during teaching learning process in the class, (2) the slow learner having special needs tend to participate passively in the matematics teaching learning process, they prefer to write the materials given by teacher rather than pay more attention, they prefer to like a calm class situation as same as the normal students’ class, and they have more learning time than normal students about three hours a day and they are helped by their mother when they got and finished their duties or homework, (3) teacher’s problems in mathematics teaching learning process in inclusive class is caused by two factors that are internal factor and external factor. Internal factors refers to the lack of the mathematics teacher’s understanding about the inclusive education and having less capability to teach the slow learner who have special need. External factors deals with there are no the special guide teachers and there are no special facilities which being prepared in mathematics teaching learning process for slow learner who have special needs.Keywords: mathematics learning process, inclusive class, slow learner.